Green modification techniques for modulating the properties and starch digestibility of rich-polyphenol low-amylose Riceberry rice (Oryza sativa L.) flour - Tai Van Ngo; Naphatrapi Luangsakul (Food Chemistry: X)
Six green modification techniques, including annealing (ANN), heat moisture treatment (HMT), pregelatinization (Pregel), ultrasound (US), wet-microwave (WM), and dry-microwave (DM), were applied to modulate the properties of rich-polyphenol low-amylose rice flour. WM produced more stable flour paste with the highest peak viscosity (246.83 ± 7.03 RVU) and swelling power (8.98 ± 1.04 g/g), and lowered digestion rate. Pregel reduced the pasting properties, led to a weak gel structure, and increased estimated glycemic index (eGI = 69.69 ± 2.69). US sample improved the solubility and increased the polyphenols bioavailability, and significantly decreased rate of digestion (eGI = 60.77 ± 0.90). ANN and HMT, altered the digestion rate of flour to be lower as presented by FTIR spectra. The previous results were confirmed by multivariate analysis. This is the first study on green modification techniques affecting the properties of low-amylose purple rice flour, opening the possibility of producing highly functional rice flour for the development of low-digestibility rice products with specific properties.